Peso Bajo e insuficiente al nacer relacionado con la prevalencia de desnutrición cróni- ca en niños de tres a seis años de las instituciones educativas iniciales Nº 162 y 171 Huaycán 2012 - Becerril Sopla, Llicely Yovany (2019)
The aim of the study was to determine the correlation between birth weight with the diagnosis of height for age inchildren three to six years in Initial Educational Institutions No. 162 and No. 171 Huaycán. The study was correlational cross-sectional, population-based study to be a unit of analysis were all preschool children aged 3 to 6 years,enrolled in educational institutions, a total of 518 students were selected by non-probability sampling as inclusioncriteria and exclusion. To collect data and use a measuring rod license growth and development of children. Fordiagnosis of height for age was based on the parameters as Waterloo and the median according to WHO tables anddata analysis was applied Chi-Square. The results were obtained from the RR population study shows that a low PN(1500g - 2500g) and insufficient (2500g - 3000g) increases to 2.9 times the risk of suffering from stunting comparedto a child with BW Normal. Also, the RR obtained from the study population shows a high PN (over 4000g) has amoderate degree of protection (0.51), to suffer from stunting compared to a child with BW Normal. Thus the correlation between birth weight with the diagnosis of height for age in the study population